Increased Expression of the Glucose Transporter Type 1 Gene Is Associated With Worse Overall Survival in Resected Pancreatic Adenocarcinoma. Issue 7 (August 2016) - Davis-Yadley, Ashley H.; Abbott, Andrea M.; Pimiento, Jose M.; Chen, Dung-Tsa; Malafa, Mokenge P.
Abstract : Objectives: There is currently no reliable method to predict the risk of relapse after curative resection of early-stage pancreatic adenocarcinoma. Increased glucose metabolism observed on 18 F-fluorodeoxyglucose positron emission tomography (PET) by malignant cells, the Warburg effect, is a well-known characteristic of the malignant phenotype. We investigated the role of glucose transporter type 1 (GLUT-1) gene expression, a glucose cell plasma membrane transporter, in early-stage pancreatic cancer. Methods: Associations between GLUT-1 gene expression with PET maximum standardized uptake values and histologic grade were investigated in early-stage pancreatic adenocarcinoma patients. Multivariate analysis was conducted to determine predictors of prognosis. Cox proportional hazard model was used for survival analysis. Results: Sixty-three patients had GLUT-1 gene analysis performed, and 50 patients had both GLUT-1 analysis and PET scan. Patients with high GLUT-1 gene expression had a decreased overall survival by univariate analysis using Cox proportional hazard model (hazard ratio, 2.82; P = 0.001) and remained significant on multivariate analysis (hazard ratio, 2.54; P = 0.03). There was no correlation of GLUT-1 gene expression with histologic grade or PET maximum standardized uptake values. Conclusions: Increased GLUT-1 gene expression was associated with a decreased overall survival in pancreatic adenocarcinoma. This supports increased GLUT-1 gene expression as a potential prognostic marker in resected pancreatic adenocarcinoma.